Implementation of green skills through the co-curriculum activities among students Technical and Vocational Education Training (TVET) towards development of Green Industry - Yapin, H.; Suhadi, N.; Esa, Ahmad (Elixir International Journal, 2017)
The concept paper discusses the implementation of green skills through co-curricular activities among students of Technical and Vocational Education Training (TVET) in line with a more sustainable industrial development towards sustainable social, economic and environmental. Implementation of green skills is assessed by its importance in education and training through co-curriculum activities as a proactive step towards a more green industrial practices benefit not only to the economy but also to support social and environmental sustainability. According to the literature, there are problems that arise due to the lack of industry awareness of the importance of the adoption of green technologies that will ultimately affect the environment. Accordingly, this article also stated that generic green skills needed by green industries as an effective method to ensure that no conflict or consistency in the implementation of green skills in TVET through co-curriculum activities towards development of green industries.